Suriname : Request for an Extended Arrangement under the Extended Fund Facility-Press Release; Staff Report; Staff Statement; and Statement by the Executive Director for Suriname. (IMF Staff Country Reports; Country Report ;, 2021)
Suriname faces systemic fiscal and external imbalances as a result of many years of economic mismanagement. Usable foreign reserves were depleted and, in the absence of other sources of budget financing, fiscal deficits were monetized. Inflation has, as a result, surged and there has been a significant depreciation of the exchange rate. Public debt, at 148 percent of GDP at end-2020, is unsustainable. In addition, there are important solvency problems embedded in the domestic banking system.